Immune gene regulation is associated with age and environmental adversity in a nonhuman primate - Marina M. Watowich; Christina E. Costa; Kenneth L. Chiou; Elisabeth A. Goldman; Rachel M. Petersen; Sam Patterson; Melween I. Martínez; Kirstin N. Sterner; Julie E. Horvath; Michael J. Montague; Michael L. Platt; Lauren J. N. Brent; et al. (Molecular Ecology, 2024)
Phenotypic aging is ubiquitous across mammalian species, suggesting shared underlying mechanisms of aging. Aging is linked to molecular changes to DNA methylation and gene expression, and environmental factors, such as severe external challenges or adversities, can moderate these age‐related changes. Yet, it remains unclear whether environmental adversities affect gene regulation via the same molecular pathways as chronological, or ‘primary’, aging. Investigating molecular aging in naturalistic animal populations can fill this gap by providing insight into shared molecular mechanisms of aging and the effects of a greater diversity of environmental adversities – particularly those that can be challenging to study in humans or laboratory organisms. Here, we characterised molecular aging – specifically, CpG methylation – in a sample of free‐ranging rhesus macaques living off the coast of Puerto Rico ( n samples = 571, n individuals = 499), which endured a major hurricane during our study. Age was associated with methylation at 78,661 sites (31% of all sites tested). Age‐associated hypermethylation occurred more frequently in areas of active gene regulation, while hypomethylation was enriched in regions that show less activity in immune cells, suggesting these regions may become de‐repressed in older individuals. Age‐associated hypomethylation also co‐occurred with increased chromatin accessibility while hypermethylation showed the opposite trend, hinting at a coordinated, multi‐level loss of epigenetic stability during aging. We detected 32,048 CpG sites significantly associated with exposure to a hurricane, and these sites overlapped age‐associated sites, most strongly in regulatory regions and most weakly in quiescent regions. Together, our results suggest that environmental adversity may contribute to aging‐related molecular phenotypes in regions of active gene transcription, but that primary aging has specific signatures in non‐regulatory regions.